2022
DOI: 10.3390/plants11192656
|View full text |Cite
|
Sign up to set email alerts
|

Antifeeding and Oviposition Deterrent Effect of Ludwigia spp. (Onagraceae) against Plutella xylostella (Lepidoptera: Plutellidae)

Abstract: Plants produce a wide variety of bioactive compounds with insecticidal properties, such as secondary metabolites capable of interfering with the nutrition and reproduction of pest species such as Plutella xylostella. Thus, the objective of this study was to evaluate the effects of aqueous and ethanolic extracts of Ludwigia spp. (Onagraceae) on the feeding and oviposition of P. xylostella. Choice bioassays were performed using aqueous and ethanolic extracts. The aqueous extract of L. tomentosa resulted in an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…H. Hara (Onagraceae) demonstrated insecticidal potential against newly emerged larvae of P. xylostella, with mortalities ranging from 14-38%(Ferreira et al 2020).Recently researchers have shown that aqueous ethanolic extract made by leaf maceration and seed oil of Triadica sebifera (L.) (Euphorbiaceae), as well as their combinations, can be recommended as anti-food to reduce damage caused by P. xylostella, and safely for predators/parasitoids under eld conditions (Dolma and Reddy 2022). In the same sense, the aqueous botanical extract by maceration, at a concentration of 10% (w/v), of L. tomentosa, resulted in a reduction of approximately 81% in the feeding of P. xylostella larvae in relation to the control(Ferreira et al 2022).…”
mentioning
confidence: 85%
“…H. Hara (Onagraceae) demonstrated insecticidal potential against newly emerged larvae of P. xylostella, with mortalities ranging from 14-38%(Ferreira et al 2020).Recently researchers have shown that aqueous ethanolic extract made by leaf maceration and seed oil of Triadica sebifera (L.) (Euphorbiaceae), as well as their combinations, can be recommended as anti-food to reduce damage caused by P. xylostella, and safely for predators/parasitoids under eld conditions (Dolma and Reddy 2022). In the same sense, the aqueous botanical extract by maceration, at a concentration of 10% (w/v), of L. tomentosa, resulted in a reduction of approximately 81% in the feeding of P. xylostella larvae in relation to the control(Ferreira et al 2022).…”
mentioning
confidence: 85%
“…After determining the consumption of each leaf disk (treated and control), the feeding deterrence index (FDI) was calculated as follows: FDI = 100{(C -T) / (C + T)}, in which C and T (Isman 1993) refer to the areas consumed on the control and treated disks, respectively. Based on the FDI, the EO solutions were classi ed as phagodeterrent (positive values) or phagostimulant (negative values) (Ferreira et al, 2022).…”
Section: Feeding Deterrence and Repellent Activity Bioassaysmentioning
confidence: 99%
“…An aqueous extract with a concentration (weight/volume) of 10%, conventional concentration, was obtained through the maceration technique and the addition of 10 g of the powdered plant material to 100 mL of distilled water by [11,19,23]. After manual stirring, the solution remained at rest for 24 h in a refrigerated environment (10 • C).…”
Section: Macerationmentioning
confidence: 99%